Barriers to Reducing Urinary Catheter Use: A Qualitative Assessment of a Statewide Initiative - Krein, Sarah L. (2013)
BACKGROUND: Preventing catheter-associated urinary tract infection (CAUTI), a common healthcare-associated infection (HAI), is important for improving the care of hospitalized patients and in meeting the goals for HAI reduction set by the U.S. Department of Health and Human Services. The objective of this study was to identify ways to enhance CAUTI prevention efforts based on the experiences of hospitals participating in the Michigan Health and Hospital Association's Keystone Center for Patient Safety statewide program to reduce unnecessary use of urinary catheters (the “Bladder Bundle”). METHODS: Qualitative assessment involving 12 purposefully sampled hospitals in Michigan. Data were collected through semi-structured phone interviews with key informants at 12 hospitals and during in-person interviews and site visits at 3 of the 12 hospitals. The analysis focused on perceptions and key issues identified by hospitals as influencing implementation of CAUTI prevention practices as recommended by the Bladder Bundle initiative. RESULTS: Common barriers to Bladder Bundle implementation and appropriate urinary catheter use were: 1) difficulty with nurse and physician engagement; 2) patient and family request for indwelling catheters; and 3) catheter insertion practices and customs in the emergency department. Strategies to address these barriers were also identified by several of the participating hospitals including: 1) incorporating urinary management (e.g., planned toileting) as part of other patient safety programs, such as a fall reduction program; 2) explicitly discussing risks of indwelling urinary catheters with patients and families; and 3) engaging with emergency department nurses and physicians to implement a process that ensures that appropriate indications for catheter use are followed. CONCLUSIONS: The Bladder Bundle provides a model for implementing strategies to reduce CAUTI. These findings provide actionable information to inform CAUTI prevention-related activities in hospitals throughout the country.